2017
DOI: 10.1016/j.nicl.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Young adolescents with autism show abnormal joint attention network: A gaze contingent fMRI study

Abstract: Behavioral research has revealed deficits in the development of joint attention (JA) as one of the earliest signs of autism. While the neural basis of JA has been studied predominantly in adults, we recently demonstrated a protracted development of the brain networks supporting JA in typically developing children and adolescents. The present eye-tracking/fMRI study now extends these findings to adolescents with autism. Our results show that in adolescents with autism JA is subserved by abnormal activation patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 93 publications
1
46
0
1
Order By: Relevance
“…In addition to primary sensory and motor regions, we also observed an increase in GWPC in parts of STS and TPJ. These regions have been extensively described as being involved in social perception and social cognition (Oberwelland et al 2017, Zilbovicius et al 2006). Our results could provide a neuroanatomical correlate for the deficits in social perceptions in patients with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to primary sensory and motor regions, we also observed an increase in GWPC in parts of STS and TPJ. These regions have been extensively described as being involved in social perception and social cognition (Oberwelland et al 2017, Zilbovicius et al 2006). Our results could provide a neuroanatomical correlate for the deficits in social perceptions in patients with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…However, these authors also reported that fractional anisotropy of longitudinal fasciculus connecting the fusiform gyrus, associated with face processing with the anterior cortical system was not associated with joint attention. Indeed, only four of the 24 studies listed in Table have reported fusiform activation in association with joint attention in studies of infants, children, and adults (Gordon et al ., ; Redcay et al ., ; Oberwelland et al ., , ). Moreover, three of those studies suggest that recruitment of fusiform activity in the joint attention tasks used in these studies was limited to familiar partners, but not present with unfamiliar partners (e.g., Oberwelland et al ., ).…”
Section: Infant Imaging and Eeg Studies Of The Neurodevelopment Of Jomentioning
confidence: 99%
“…Oberwelland et al . () went on to employ their virtual joint attention imaging paradigm to examine the joint attention system of adolescents with ASD. They found that adolescents with ASD displayed behavioral evidence of IJA and RJA that was comparable to typical controls, but they did not display the same level of neural system specialization for joint attention as did the controls.…”
Section: Imaging Joint Attention In Children With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social deficits in communication and inter-personal interactions, as well as non-social deficits in repetitive behavior (61). Social deficits in communication in individuals with ASD are reflected in various aspects, such as joint attention (62)(63)(64), motor imitation (65), and interpersonal coordination (66,67).…”
Section: Recent Applications Of the Two-person Approach In Social Intmentioning
confidence: 99%